Characterization of the microscopic tribological properties of sandfish (Scincus scincus) scales by atomic force microscopy - Wu, Weibin; Lutz, Christian; Mersch, Simon; Thelen, Richard; Greiner, Christian; Gomard, Guillaume; Hölscher, Hendrik (Beilstein Journal of Nanotechnology, 2018)
Lizards of the genus Scincus are widely known under the common name sandfish due to their ability to swim in loose, aeolian sand. Some studies report that this fascinating property of sandfish is accompanied by unique tribological properties of their skin such as ultra-low adhesion, friction and wear. The majority of these reports, however, is based on experiments conducted with a non-standard granular tribometer. Here, we characterise microscopic adhesion, friction and wear of single sandfish scales by atomic force microscopy. The analysis of frictional properties with different types of probes (sharp silicon tips, spherical glass tips and sand debris) demonstrates that the tribological properties of sandfish scales on the microscale are not exceptional if compared to snake scales or technical surfaces such as aluminium, Teflon, or highly oriented pyrolytic graphite.
Keywords: biotribology; frictional properties of reptile scales; sandfish; Scincus scincus